Ritual participation? Polish opinions on politics and political parties - Solarz, Radosław (Political Preferences, 2013)
Poles comparatively low political activity, continued from the first competitive parliamentary election in 1991, leads to take a reflection of the voters perception of politics and political parties. The article focus on the percep- tion of political parties in Poland and the Poles' attitude to politics. Research has shown that the political sphere of democratic Poland separates from the social life. The activities of political parties, political conflicts and their solutions, are a phenomena that the majority of Poles do not care about. Polish political institutions and democratic procedures act in a specific social void. Poles political behavior (especially the voters one), in the period of democratic system, is characterized by high level of ritualism. This method of adaptation of the citizens of Poland to the democratic political system leads to low level of trust in political institutions.